(untitled) (Revista Ciência Agronômica, 2023)
The aim of this study was to evaluate the relative expression of two candidate genes, CYP (cyclophilin) and Arabinogalactan, possibly involved with seed quality, in contrasting soybean seed coats. The following genotypes were used: BMX Potência RR and CD 202, both with yellow coats, and TP and IAC, with black coats. The relative expression of the genes was evaluated by qPCR in seven development phases of the coats of the four genotypes at 25; 30; 35; 40; 45; 50 and 55 days after anthesis. The design was completely randomized, with three replicates. The data were submitted to analysis of variance and the means were compared via the Scott Knott test, at 5% probability. The CYP gene showed greater expression in the intermediate stages of development of the coats of the genotypes CD 202 and IAC, yellow coat and black coat, respectively. The A rabinogalactan gene presented greater expression in the final stages of coats development of BMX Potência RR.